Hubungan Antara Humor Dengan Hubungan Interpersonal Karyawan - Haryo Susilo, Firman; , Dra Zrotul uyun, M. Si., Psi.ah (2016)
ABSTRACT The aim of this research is to know correlation between humor and employee's interpersonal relationship. This research was held at SKPD Tegal regency. Participants of this research are 93 Tegal regency's civil servants. It used non-random quota sampling technique. This research used quantitative methode and used tools they are interpersonal scale and humor scale. To analyze data, researcher used product moment correlation by Pearson. From the result of analitical data showed the value of correlation coefficient (rxy)= 0,130 with the value of signification = 0,107 (p < 0,05) that means there were no correlation between humor and employee's interpersonal relationship. Interpersonal relationship included in high category, while humor included in medium category. Keywords: humor, interpersonal relationship